Penguatan Kapasitas UMKM Dalam Sertifikasi Halal Melalui Pendampingan Teknologi Aplikasi Sihalal Di Kota Bogor - Sukamto, Anton; Nurachmad, Edi; Mulyana, Ade; Hendrawan, Didit; Sugiarto, Ade Antoni; Wandika, Daffa Rizqi (Jurnal Abdimas Dedikasi Kesatuan, 2026)
The potential of the halal market in Indonesia continues to grow; however, this development has not been fully matched by the readiness of micro, small, and medium enterprises (MSMEs), particularly in fulfilling halal certification requirements. In the City of Bogor, MSME actors in the food and beverage sector still face challenges in the form of limited understanding of halal regulations, inadequate business administration, and low levels of technological literacy. This community service program aims to strengthen the capacity of MSMEs to obtain halal certification through technology-based assistance utilizing the SiHalal application. The implementation methods include socialization of halal regulations, training on the use of the SiHalal application, and continuous assistance in preparing business legality documents, the Halal Product Assurance System (SJPH), as well as verification and validation processes until the certification is completed. The results of the program indicate an improvement in partners’ understanding of halal certification procedures, their ability to independently operate the SiHalal application, and the readiness of their business administrative documents. This program contributes to enhancing MSME competitiveness and expanding market access, and therefore may serve as an effective assistance model for strengthening the local halal industry ecosystem. Keywords: MSMEs, Halal Certification, SiHalal, Technology-Based Assistance, Bogor City